Fostering public trust in science: The role of social media. (October 2019) - Huber, Brigitte; Barnidge, Matthew; Gil de Zúñiga, Homero; Liu, James
The growing importance of social media for getting science news has raised questions about whether these online platforms foster or hinder public trust in science. Employing multilevel modeling, this study leverages a 20-country survey to examine the relationship between social media news use and trust in science. Results show a positive relationship between these variables across countries. Moreover, the between-country variation in this relationship is related to two cultural characteristics of a country, individualism/collectivism and power distance.